Fundepar: caso único de investimento de capital semente em empresas nascentes de origem acadêmica no Brasil - Ramon Dias de Azevedo (2018)
The development of spin-offs is able to generate great impacts for the economy of a region and a country, bringing technological development, new jobs, export and wealth. However, the process of generating and developing this kind of business and, consequently, technology transfer from the universities and research centers for the market, is complex and risky. This process demands at least access to relevant market information, to capital for financing such as the pre-launch and post-launch operation, support of the university or research center that originated the spin-off for development of technologies and a team with business and technical profile. Fundepar was established in this scenario, as a pioneer initiative in Brazil, with the objective of catalyzing the process of developing spin-offs by investing seed money and supporting the management and growth of these companies. The present study describes the way to establish the Fundepar company, the legal structure, the strategy, the processes of analysis of investments, negotiation, investment decision and development of the invested companies. In addition, its value proposition, its differentials, and its results obtained so far were discussed, aiming to make possible the expansion and evolution of the model, and also its replication. To achieve this objective, a single case study design was used, collecting and analyzing detailed qualitative and quantitative data available. After the description of the case, the results analysis was carried out from a perspective of Fundep, its controller company, and the impacts for innovation ecosystem in general, in addition to the comparison with available indicators of a Brazilian seed capital fund that has invested in some spin-offs in recent years. This study presents the case of Fundepar, a successful initiative of an innovative investment model to support the generation and growth of spin-offs of academic origin, which may be an alternative to current investment models in Brazil, contributing to transfer of knowledge from academia to society, and able to generating a great impact for Brazilian economic development.